Efforts to Improve Employee Performance Through Communication And Leadership Style In PT J&T Express Medan - Ina Namora Putri Siregar; Suryani (International Journal of Science, Technology & Management, 2021)
PT J&T Express is a service company engaged in the delivery of goods. Decreased employee performance can be seen from the decreased ability of employees to meet delivery targets which is influenced by inefficient communication among fellow employees and the lack of a leader's role in motivating employees to work more optimally. The method used in this research is a quantitative approach, this type of research is descriptive quantitative. Methods of collecting data were interviews, questionnaires, and documentation. The data analysis method used is multiple regression. The population and research sample amounted to 157 employees of PT J&T Express. The results of research on communication and leadership style simultaneously and partially have a positive and significant effect on employee performance at PT J&T Express. The leadership style variable has a more dominant influence than communication in improving employee performance. Finally, the magnitude of the coefficient of determination is 0.587. This means that 58.7% of employee performance can be explained by Communication and Leadership Style while the remaining 41.3% is explained by other variables.